The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.tate.2004.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Teaching a foreign language: one teacher's practical theory

Abstract: In recent decades, teachers of second languages in many countries, including Australia, have been encouraged to use an approach known as Communicative Language Teaching (CLT). This approach advocates the development of communicative competence as a primary goal through the extensive use of the second language as a means of communication during classroom lessons. Understandably, education authorities and teacher educators are keen to know what teachers understand by CLT and how well they have incorporated this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 21 publications
(18 reference statements)
1
41
0
2
Order By: Relevance
“…Miller & Aldred 2000;Mangubhai et al 2004Mangubhai et al , 2005Nazari 2007). The contradictory results of research on Communicative Language Teaching (CLT) and teacher stereotypes are thought-provoking.…”
Section: Approaches To Teachingmentioning
confidence: 99%
“…Miller & Aldred 2000;Mangubhai et al 2004Mangubhai et al , 2005Nazari 2007). The contradictory results of research on Communicative Language Teaching (CLT) and teacher stereotypes are thought-provoking.…”
Section: Approaches To Teachingmentioning
confidence: 99%
“…The mixed methods approach adopted in this study aimed to investigate teacher understanding of Afrikaans FAL and their classroom practice in this regard. Like in a similar study conducted by Mangubhai et al (2004), this research was used to source FAL teachers' knowledge of language policies and methods and how these different kinds of knowledge influence the teachers' choice of methods and classroom practice. Mangubhai et al (2004) state that what teachers do in classrooms is guided by the practical knowledge that they have built up largely through experience in classrooms.…”
Section: Mixed Methods Research Designmentioning
confidence: 99%
“…Like in a similar study conducted by Mangubhai et al (2004), this research was used to source FAL teachers' knowledge of language policies and methods and how these different kinds of knowledge influence the teachers' choice of methods and classroom practice. Mangubhai et al (2004) state that what teachers do in classrooms is guided by the practical knowledge that they have built up largely through experience in classrooms. Because practical knowledge is a product of a natural tendency in human beings to try to make sense of the contexts in which they work and live and is used to build framework for guiding action therein, it can also take on the form of practical theory (2004: 293).…”
Section: Mixed Methods Research Designmentioning
confidence: 99%
“…Over the past 30 years, research has suggested that teachers' beliefs heavily influence their pedagogical practice (e.g., Borg, 2003;Mangubhai et al, 2004;Ng & Farrell, 2003), their instructional decisions in the classroom (Tillema, 2000), and acceptance and uptake of new approaches, techniques and activities (Donaghue, 2003).…”
Section: Introductionmentioning
confidence: 99%